Rotavirus encephalopathy with concomitant acute cerebellitis: report of a case and review of the literature - Paketçi, Cem; Edem, Pınar; Okur, Derya; Sarıoğlu, Fatma Ceren; Güleryüz, Handan; Bayram, Erhan; Kurul, Semra Hız; Yiş, Uluç (The Turkish Journal of Pediatrics, 2020)
Rotavirus is a leading cause of gastroenteritis in children under 5 years of age. It is known that neurological manifestations like seizures, encephalopathy and encephalitis can rarely be seen due to rotavirus infections. Cerebellar involvement is extremely rare. We present an uncommon neurological manifestation of rotavirus infection in a 4-year-old Turkish child who presented with hypotonia, reduced consciousness and mutism. Magnetic resonance imaging revealed diffusion abnormalities in the splenium of corpus callosum and nucleus dentatus bilaterally. She was diagnosed with rotavirus cerebellitis. She improved well with dexamethasone and intravenous immunoglobulin but still has dysarthria and poor fine motor coordination.
Keywords: central nervous system infection; encephalitis; encephalopathy; mutism; rotavirus